Green logistics for sustainable development in Vietnam - Trần Thị Kim Liên (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
Sustainable, innovative development has become a goal for many countries worldwide, and Vietnam is no exception. To achieve this goal, many countries have been applying "greening" strategies to develop their economic sectors, including logistics. In Vietnam, logistics costs account for approximately 20.9% to 25% of GDP, with transportation contributing 50% to 60% (WB, 2021). This indicates that it is a major cause of environmental pollution, leading to increased carbon emissions and reliance on fossil fuels. Therefore, "greening" various sectors of the economy, particularly focusing on the development of green logistics, has become a core foundation for Vietnam’s sustainable development.